A Case of Choroidal Osteoma - Baniya, Pooja; Singh, Pragya; Phauja, Shristi; Sapkota, Samana; Subedi, Dipesh; Shrestha, Anju (International Journal of Silkroad Institute of Research and Training, 2024)
Choroidal osteoma is a rare benign ossifying tumor of the choroid, predominantly affecting healthy young females. This report presents a case of a 73-year-old female with no significant systemic or ocular history, except for prior cataract surgery. The patient presented with irritation and itching, and examination revealed a hypopigmented lesion inferior to the optic disc in the left eye, consistent with choroidal osteoma. Diagnosis was confirmed via fundus examination, B-scan ultrasonography, and OCT. The lesion displayed elevated retinal pigment epithelium but no subretinal fluid or membrane. Management included cataract surgery with guarded visual prognosis, and regular follow-up for potential choroidal neovascularization. The patient’s visual acuity improved postoperatively. Choroidal osteoma typically results in vision loss through atrophy of the overlying retinal pigment epithelium or choroidal neovascularization. Treatment options for associated complications include photodynamic therapy and anti-VEGF agents. This case emphasizes the importance of monitoring for progressive changes in patients with choroidal osteoma.